2021
DOI: 10.1080/09658416.2021.1905655
|View full text |Cite
|
Sign up to set email alerts
|

Metatalk and metalinguistic knowledge: the interplay of procedural and declarative knowledge in the classroom discourse of first-language grammar teaching

Abstract: High-quality talk' is a fundamental principle of many approaches to teaching grammar. However, relatively few studies have attempted to characterize this talk with attention to the ways in which classroom dialogue might engender metalinguistic thinking. This paper explores how the concepts of procedural and declarative metalinguistic knowledge may be applied to classroom discourse in order to identify the problems and potentials of grammatical 'Metatalk' . The data is drawn from observations of functionally-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Some researchers have documented a number of empirical investigations on classroom discourse [13][14][15][16]. Weninger's study of classroom discourse [16] examines English classes that used a critical literacy unit.…”
Section: Classroom Discoursementioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have documented a number of empirical investigations on classroom discourse [13][14][15][16]. Weninger's study of classroom discourse [16] examines English classes that used a critical literacy unit.…”
Section: Classroom Discoursementioning
confidence: 99%
“…A study [15] has also reported an extensive study of classroom discourse. The goal of this study is to explore the opportunities and challenges of grammatical metatalk in classroom discourse by examining procedural and declarative metalinguistic knowledge.…”
Section: Classroom Discoursementioning
confidence: 99%
“…However, it is possible to express metalinguistic understanding without the use of metalinguistic terms (Myhill et al, 2019). MT provides teachers with opportunities to assess, guide and model the expression of metalinguistic understanding (Watson et al, 2021). …”
Section: Theoretical Framingmentioning
confidence: 99%
“…Declarative knowledge can be made overt or explicit, "teachable" knowledge that is statically stored in memory (Ullman, 2005). This is conceptual or descriptive knowledge, as opposed to "implicit" knowledge, or knowledge of performance or operation (Watson et al, 2021). It is therefore hypothesized that bilingual learners transfer knowledge from their L1 to perform academically in the L2 (Olivares, 2002).…”
Section: The Role Of the First Language In Academic Success In Englis...mentioning
confidence: 99%